BOOK SEARCH PROGRAM APPLICATIONS IN EAST JAKARTA MUNICIPALITY PUBLIC LIBRARY USING VB 6.0 - Dian Narulitasari; Yulina Yulina, SKom, MMSi (Jurnal Sistem Informasi, 2004)
This application is to facilitate the search as effective as da book as efficiently aspossible without having to manually search for a list of books that will take a longtime. With this application, it is expected to improve service to readers. So that thereader in search of books can be done with the help of media premises fast computerthrough Visual Basic 6.0.